Predeco program and its effectiveness on interpersonal relationships in high school students - Gutiérrez Ulloa, Cristian Raymound; Cordova Castillo, Carlos Wilfredo; Acosta Enriquez, Benicio Gonzalo; Villena Zapata, Luigi; García Salirrosas, Liz Maribel; Vilcapoma Pérez, César Robin; López Roca, Carlos (LACCEI, 2023)
Interpersonal relationships can have a significant impact on students' educational experience, and positive relationships can foster a sense of community, mutual support, and collaboration, which can improve students' academic performance and motivation. The study aimed to determine the effectiveness of the implementation of the “Predeco” program on the interpersonal relationships of high school students in 2021. The study followed the quantitative approach and pre-experimental design. The sample consisted of 30 students selected from non-probabilistic sampling, who were given a questionnaire validated by experts and subjected to reliability criteria. The results show that the application of the “Predeco” program significantly improved (p=0.000000875